2019
DOI: 10.3389/fneur.2019.01023
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Whole-Body Vibration on the Postural Organization of Gait Initiation in Young Adults and Elderly: A Randomized Sham Intervention Study

Abstract: Whole-body vibration (WBV) is a training method that exposes the entire body to mechanical oscillations while standing erect or seated on a vibrating platform. This method is nowadays commonly used by clinicians to improve specific motor outcomes in various sub-populations such as elderly and young healthy adults, either sedentary or well-trained. The present study investigated the effects of acute WBV application on the balance control mechanisms during gait initiation (GI) in young healthy adults and elderly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 97 publications
1
10
0
Order By: Relevance
“…Thus, it is vital to develop the measures aimed at creating a safe living environment for people of middle and old ages, which would favorably affect their QoL and the process of successful aging. Our findings reinforced an importance and effectiveness of exercise to strengthen leg muscles and joints, as well as back muscles, in older adults predisposed to falls as a criterion for QoL and successful aging process [14]. We established the relations between the speed-time performance of monotonous and complex modes of walking, and SEA perception in the elderly women with falls.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Thus, it is vital to develop the measures aimed at creating a safe living environment for people of middle and old ages, which would favorably affect their QoL and the process of successful aging. Our findings reinforced an importance and effectiveness of exercise to strengthen leg muscles and joints, as well as back muscles, in older adults predisposed to falls as a criterion for QoL and successful aging process [14]. We established the relations between the speed-time performance of monotonous and complex modes of walking, and SEA perception in the elderly women with falls.…”
Section: Discussionsupporting
confidence: 75%
“…These findings suggested that emergence of high trait anxiety could impair complex movement acts parameters in older women. The results showed that decreased functions of the knee joint extensor mechanism, along with decreased monotonous walk and complex movement acts, would adversely affect the QoL parameters [8,14]. The parameters of walking in old and senile age would affect psychoemotional state and QoL [19].…”
Section: Discussionmentioning
confidence: 99%
“…Baevsky, allows assessing the state of the adaptive compensatory activity of the entire body. It has become widespread due to its simplicity, accessibility and high information content [10,15,23]. The results of this method for HRV assessment also did not reveal statistically significant differences between the group of elderly women and the comparison group.…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies pointed to the contribution of the ANS to the maintenance of postural balance. E.g., the data of some studies demonstrated that the ANS can contribute to a coordinated compensatory postural response and to maintaining a proper postural balance [10,15]. Also, one of the informative methods for studying the neurophysiological mechanisms of human brain activity is the mathematical analysis of electroencephalograms (EEG), in particular, EEG spectral analysis and EEG coherence analysis that reflect the measure of the functional connection between regions of the cerebral cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, vibration can be applied directly (local vibration) to the muscle [ 17 , 23 ] or indirectly using vibrating platforms (e.g., whole-body vibration, WBV). The use of WBV in conjunction with exercise has been studied in randomized clinical trials [ 24 , 25 , 26 ], but thus far, no comprehensive review evaluating specific interventions and protocols, especially in the case of older adults has appeared in the Cochrane Library. A review published in 2019 by Leite et al [ 27 ] suggested there is not enough evidence to support the use of WBV in clinical practice among people with various disabilities [ 27 ].…”
Section: Introductionmentioning
confidence: 99%